A feminist defense of pornography - McElroy, Wendy (Free Inquiry, 1997)
Keywords: approches et analyses; cours; intersectionnalité; point de vue situé; pornographie; premier cycle; ressource en ligne; sex1911; sexualité; thématiques

XXX: a woman's right to pornography - McElroy, Wendy (St. Martin's Press, 1995)
An unconventional argument for the preservation of pornography asserts that pornography can serve to benefit the feminist movement and promote sexual freedom for women, and explores the historical relationship between women and pornography.
Keywords: corps; cours; droits des femmes*; pornographie; premier cycle; sex1911; sexualité; thématiques